Objectively measured 24-h movement behaviours of child-guardian pairs in low-to-middle income households in Nairobi City County, Kenya - Lucy-Joy Wachira; Nils Swindell; Noora Kanerva; Muhoro Munuhe; Timo Vuorimaa; Tiina Laiho; Sophie Ochola; Maijaliisa Erkkola; George Owino; Gareth Stratton; Mikael Fogelholm; Vincent Onywera (Sports Medicine and Health Science)
Background: The decreasing prevalence of physical activity (PA) among urban children in Sub-Saharan Africa is a growing public health concern. More emphasis should focus on examining the influence of parental PA behaviour on the children’s PA patterns. We explored associations of 24 ​hour (h) accelerometer-measured movement behaviours of guardian-child pairs in Nairobi City County, Kenya. Methods: This cross-sectional study assessed 80 pairs consisting of children aged 9–14 years and their guardians in one area of low and one area of middle socioeconomic status (SES) (Embakasi Sub-County and Lang’ata Sub-County), in Nairobi City County, Kenya. The study used waist worn Tri-axial Actigraph (GT3X+ and ActiSleep+) accelerometers to quantify PA and sedentary time (SED). Association between guardians' and children’s PA was examined using linear regression, adjusting for guardians' educational attainment and household wealth. Results: Of the children, 42 (52.5%) and 76 (96.2%) of the guardians were women. Children in low SES areas spent more time (p ​< ​0.001) in moderate-to-vigorous physical activity compared to children from middle SES area. The guardians in low SES area were younger and spent more time in light PA (p ​= ​0.036) while their counterparts had higher daily SED (p ​= ​0.049). Guardian’s SED associated with higher children’s SED (p ​= ​0.033) even after adjusting for guardians' educational attainment (p ​= ​0.032) and wealth (p ​= ​0.05). There was no association between guardians' and children’s MVPA. Conclusion: Considered alongside the extant literature, these results suggest that health promotion strategies should aim to reduce parental SED time while also planning to increase children’s PA.